Quality gradient of salbutamol sulphate preparations available in Bangladesh markets - Islam, Md Shariful; Muhsin, Mohammad Didare Alam; Feroz Uddin, AY Sk; Chowdhury, Ahmed (Jahangirnagar University Journal of Biological Sciences, 2016)
Abstract not available Jahangirnagar University J. Biol. Sci. 4(1): 85-89, 2015 (June)